Inclusive engineering identities: two new surveys to assess first-year students' inclusive values and behaviors - Rambo-Hernandez, Karen E., author; Atadero, Rebecca A., author; Paguyo, Christina H., author; Schwartz, Jeremy C., author; ASEE, publisher (Colorado State University. Libraries, 2017)
The under-representation of women and people of color in engineering careers is not fully explained by their lower representation in engineering degree programs. There is also attrition from the profession after engineering degrees are earned. Currently, 20% of engineering degrees are awarded to women, and only 13% of the engineering workforce are women. Also, underrepresented minorities earn a small proportion of the science, technology, engineering, and mathematics (STEM) degrees, and represent an even smaller proportion of the workforce. For example, while approximately 11% of the total workforce is Black, only 6% of the STEM workforce is Black (U.S. Department of Education, 2016). Often cited issues for leaving engineering are uncomfortable and unsupportive work climates (Singh, Fouad, Fitzpatrick, & Chang, 2014). Women who have earned bachelors degrees in engineering left engineering at much higher rates than men, and these women cite issues of poor workplace climates, bosses, or culture (Singh et al. 2014). Women who stayed in engineering cite being supported by their organizations and perceiving their work as valued (Singh et al. 2014). More recent research demonstrated this uncomfortable culture exists well before entering the workforce. Undergraduate women cite informal interactions and sexism in teams as propagating a culture that is unwelcoming to women (Seron, Silbey, Cech, & Rubineau, 2016). Most efforts to change these percentages of representation both in the workforce and in school focus exclusively on those in the minority. However, our NSF funded study seeks to change the culture of engineering to be more welcoming and supportive of women and underrepresented minorities by helping all engineers appreciate and seek out diversity In our project we have worked with several instructors to infuse first year engineering classes with activities to promote diversity and inclusion. By working towards cultural change we hope to impact both university degree programs and engineering practice. We developed intervention activities for first-year engineering courses to promote what we termed an inclusive engineering identity. Inclusive engineering identity is displayed by engineers who value diversity in engineering and promote inclusive behaviors within the profession. When we tried to measure the impact of our intervention on all engineering students, we quickly discovered there were no psychometrically sound measures to assess how engineering students valued diversity specifically in the context of engineering and how likely they were to enact inclusive behaviors. Thus, this research study details the development of two new scales to measure how students develop an inclusive engineering identity.
Paper given at the ASEE's 124th Annual Conference & Exposition in Columbus Ohio, USA, June 25-28, 2017.
Paper ID #18467.
Keywords: engineering education; diversity in engineering; first-year engineering students; engineering identity; women; underrepresented minorities; inclusive engineering; engineering curriculum